Activity in motor–sensory projections reveals distributed coding in somatosensation - Petreanu, Leopoldo; Gutnisky, Diego A.; Huber, Daniel; Xu, Ning-long; O’Connor, Dan H.; Tian, Lin; Looger, Loren; Svoboda, Karel (Nature (London), 2012)
Imaging of activity in long-range axons is reported in mice performing tactile object-localization with their whiskers; the feedback projection from the motor cortex to the somatosensory cortex provides information to integrate whisker movement information and touch, which are key components of object identification. Touch perception by a whisker When rodents explore objects with their whiskers, touch signals are represented in the somatosensory cortex, and are also sent, by projections, to the motor cortex. The motor cortex also projects back into the somatosensory cortex, potentially providing whisker-movement information for integration with touch signals. This study addresses the question of what the motor cortex actually tells the somatosensory cortex. Karel Svoboda and colleagues imaged activity in the motor neuron axonal arbors of the somatosensory cortex while mice were performing an object-localization task that required integration of movement with touch and other senses. The resulting images show axons representing a diverse range of signals, including whisker movements and touch. Cortical-feedback projections to primary sensory areas terminate most heavily in layer 1 (L1) of the neocortex 1 , 2 , where they make synapses with tuft dendrites of pyramidal neurons. L1 input is thought to provide ‘contextual’ information 3 , but the signals transmitted by L1 feedback remain uncharacterized. In the rodent somatosensory system, the spatially diffuse 4 feedback projection from vibrissal motor cortex (vM1) to vibrissal somatosensory cortex (vS1, also known as the barrel cortex) may allow whisker touch to be interpreted in the context of whisker position to compute object location 5 , 6 . When mice palpate objects with their whiskers to localize object features 7 , 8 , whisker touch excites vS1 9 and later vM1 in a somatotopic manner 10 , 11 , 12 , 13 . Here we use axonal calcium imaging to track activity in vM1→vS1 afferents in L1 of the barrel cortex while mice performed whisker-dependent object localization. Spatially intermingled individual axons represent whisker movements, touch and other behavioural features. In a subpopulation of axons, activity depends on object location and persists for seconds after touch. Neurons in the barrel cortex thus have information to integrate movements and touches of multiple whiskers over time, key components of object identification and navigation by active touch.